Drug‐induced hypersensitivity syndrome/drug rash with eosinophilia and systemic symptoms due to diaminodiphenylsulfone during the treatment of pemphigus foliaceus. Issue 5 (3rd May 2021) - Honobe, Akiko; Mitsui, Hiroshi; Kinoshita, Manao; Shimizu, Takae; Sano, Shinya; Shimada, Shinji; Kawamura, Tatsuyoshi
Abstract : We presented a case of DDS‐induced DIHS/DRESS. Genetic examination revealed that our patient held human leukocyte antigen (HLA)‐B*13:01.